Effect of temperature change on physiology and biochemistry of algae: a review - Teoh, Ming-Li; Chu, Wan-Loy; Phang, Siew-Moi (Malaysian Journal of Science, 2010)
The productivity and survival of algae are strongly affected by their physiological and biochemical processes, as well as biotic and abiotic factors in the environment. In recent years, global climate change such as increased temperature and elevated ultraviolet radiation (UVR) due to ozone depletion has huge impact on organisms particularly the ones in the marine ecosystem. It has been demonstrated that the global temperature increased steadily over the last decade, with an average of 0.74°C. In the coming years, climate model projections summarized by the Intergovernmental Panel of Climate Change (IPCC) indicate that average global surface temperature will likely rise a further 0.5 to 1.6°C by 2030, and rising to 1.1 to 6.4°C by 2100. As algae serve as the primary producer of food chain in both marine and terrestrial ecosystems, it is of great significance to understand the impact of temperature change on their physiological and biochemical processes. This review provides the information on how algae respond to temperature change based on their growth, biochemical composition and fatty acid composition.